Identify Traffic Congestion Using Speed Data Measured By Gis, GpsTechnique - Ataiwe, Tariq; Salman, Nawal; Ismael, Hameed (Iraqi Journal of Science, 2024)
With the rapid vehicle volume growth on roads, the performance of urban roadtraffic systems is a major concern to transportation planners, road users, and allmembers of the urban community. The evaluation of the performance measuresrelies on the accuracy and reliability of the collected traffic data.This study investigates traffic speed measurement using GPS technique for parts ofAl-Karada Khareeg road by identify the congested segments. The collected GPSpoints were mapped to the highway using "Arc Map 10" program in a GISenvironment. Travel time, speed and congestion index values were measured alongselected highway segments for evaluating the traffic condition of the highways. Thebenefit of this way is simple, and easy to understand.